BUILDING BASIC SCIENCE CONCEPTS THROUGH SIMPLE EXPERIMENTS AT AISYIYAH BUSTANUL ATHFAL 2 KINDERGARTEN (PIONIR: JURNAL PENDIDIKAN, 2025)
Introduction of basic science concepts to early childhood is very important to stimulate curiosity, develop critical thinking skills, and build an initial understanding of natural phenomena. This article aims to explore the use of simple experimental methods as a means to build basic science concepts in Aisyiyah Bustanul Athfal 2 Kindergarten. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of experimental activities, such as mixing colors and observing the properties of objects. The results showed that simple experiments that were designed in a safe, interesting, and easy-to-understand way were able to increase children's engagement, strengthen their understanding of basic science concepts, and encourage questioning and experimenting activities. In conclusion, simple experiments are an effective learning strategy in supporting the cognitive development and curiosity of early childhood. These findings can be adapted by other PAUD educators by adjusting the context and characteristics of children in each learning environment. In addition, this approach is relevant to the principles of active and constructivist learning in early childhood education, so that it can enrich pedagogical practices at the national and global levels.Keyword: Simple Experiments, Basic Concepts of Science, Early Childhood Education, Aisyiyah Bustanul Athfal Kindergarten, Play-Based Learning